2016
DOI: 10.3168/jds.2016-11467
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing flora balance in the gastrointestinal tract of mice by lactic acid bacteria from Chinese sourdough and enzyme activities indicative of metabolism of protein, fat, and carbohydrate by the flora

Abstract: In this study, we investigated the effect of administration of 5 strains of lactic acid bacteria (LAB) isolated from traditional Chinese sourdough on the flora balance of gastrointestinal tract of mice. We specifically measured Enterococcus, Enterobacter, Bacteroides, and Lactobacillus by plate count and real-time PCR methods, and α-glucosidase, lactate dehydrogenase, esterase, and aminopeptidase activities as indicative of metabolism of sugar, fat, and protein from LAB isolated from feces of mice in vitro. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
12
0
2
Order By: Relevance
“…The constructed model of the hyperuricemia mice efficiently elevated serum UA in mice more stably, compared with oteracil potassium or high purine diet alone to sustain a longer duration of hyperuricemia. 26,34,35 Thus, this method was adopted to construct hyperuricemia mice and gavaged with the strain (Figure 3b). Feces of mice were collected to investigate the survival of JL-3.…”
Section: Jl-3 Decreases Ua Level In Hyperuricemic Micementioning
confidence: 99%
See 1 more Smart Citation
“…The constructed model of the hyperuricemia mice efficiently elevated serum UA in mice more stably, compared with oteracil potassium or high purine diet alone to sustain a longer duration of hyperuricemia. 26,34,35 Thus, this method was adopted to construct hyperuricemia mice and gavaged with the strain (Figure 3b). Feces of mice were collected to investigate the survival of JL-3.…”
Section: Jl-3 Decreases Ua Level In Hyperuricemic Micementioning
confidence: 99%
“…For inducting of UA-induced hyperuricemia, mice were given oteracil potassium (OP) and UA in 0.5 mL water for 14 d. Fifty mice were randomly divided into five groups, where OP and UA were used to construct the hyperuricemia animal model according to literature. 34,79 The control group was then fed with a basal diet, and orally gavaged with 0.5 mL of water, while the UA 1 group was given the basal diet along with OP (4%) and UA (1%) injection through the oral gavaged route. The UA 2 group was also given the basal diet of OP (4 %) and UA (2 %), which were injected through the oral gavaged route, while the UA 3 group was fed the basal diet and intraperitoneally injected with OP (4%) and UA (2%) in 0.5 mL water.…”
Section: Experimental Design Based On the Animal Modelmentioning
confidence: 99%
“…They are also known to improve the microfloral balance in gastrointestinal tract; for example, Lb. fermentum is shown to strengthen it possibly through the increased activity of α-glycosidases and esterases 11 . In a different study, it is reported that a L. mesenteroides strain produces the prebiotic isomaltooligosaccharides that in turn enhance the growth of Bifidobacterium and Lactobacillus species in poultry chicken 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the proportion of the intestinal microbiota differs between healthy individuals and those who are not. The diversity of the intestinal microbiota in patients with chronic kidney disease is lower, and the LAB strains affect liver and kidney function by changing the composition of the microbiota [ 31 ]. We previously found that the structure of the intestinal flora of mice treated with mixed LAB was restored and the symptoms of S. aureus infection improved [ 10 ], indicating that intestinal health was associated with disease recovery.…”
Section: Discussionmentioning
confidence: 99%